2023
DOI: 10.3390/medicina59040742
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter 2 (SGLT2) Inhibitors: Harms or Unexpected Benefits?

Abstract: There is a need for innovative pharmaceutical intervention in light of the increasing prevalence of metabolic disease and cardiovascular disease. The kidneys’ sodium-glucose cotransporter 2 inhibitors (SGLT2) receptors are targeted to reduce glucose reabsorption by SGLT2. Patients with type 2 diabetes mellitus (T2DM) benefit the most from reduced blood glucose levels, although this is just one of the numerous physiological consequences. To establish existing understanding and possible advantages and risks for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…These drugs also help lower blood pressure, promote weight loss, improve arterial function, and reduce inflammation. Another conducted by Chesterman et al [12] supports the findings of Andreea et al [11] and reveals that SGLT2 inhibitors have emerged as a valuable therapeutic option for the treatment of cardiovascular disorders [41]. The clinical trials and real-world evidence show that these medications can reduce the risk of major adverse cardiovascular events, including heart attacks, strokes, and cardiovascular death.…”
Section: Comparison With the Existing Literaturementioning
confidence: 68%
See 2 more Smart Citations
“…These drugs also help lower blood pressure, promote weight loss, improve arterial function, and reduce inflammation. Another conducted by Chesterman et al [12] supports the findings of Andreea et al [11] and reveals that SGLT2 inhibitors have emerged as a valuable therapeutic option for the treatment of cardiovascular disorders [41]. The clinical trials and real-world evidence show that these medications can reduce the risk of major adverse cardiovascular events, including heart attacks, strokes, and cardiovascular death.…”
Section: Comparison With the Existing Literaturementioning
confidence: 68%
“…The study conducted by Andreea et al [ 11 ] revealed that the SGLT2 inhibitors offer unexpected benefits beyond their glucose-lowering effects. The findings of these drugs indicate that these medications provide significant cardiovascular benefits, including reducing the risk of major adverse cardiovascular events, such as heart attacks, strokes, cardiovascular death, etc.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The approval of these novel glucose-lowering agents began in 2013 and since then, six SGLT2 inhibitors have been approved for the treatment of T2DM by the FDA and EMA: empagliflozin, dapagliflozin, canagliflozin, ertugliflozin, bexagliflozin, and sotagliflozin [31]. Their cardioprotective mechanisms can be explained by an increase in distal tubular sodium load, inhibiting the renin-angiotensin system (RAS) and reducing preload (natriuresis and diuresis) and afterload (arterial vasodilatation).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the positive impact of GLP-1 drugs on weight loss and appetite control is confirmed, enabling obesity treatment to be more effective. Due to the adverse effects of obesity on psoriasis and PsA, these drugs could indirectly improve both conditions [ 84 ]. Thus, GLP-1 analogs may be a suitable option for obese patients with PsA due to their ability to diminish low-grade inflammation caused by excessive fat tissue.…”
Section: Diabetes Mellitus Type 2 Treatment In Psa Patientsmentioning
confidence: 99%